Limoneno complexado atenua a nocicepção orofacial com participação das vias PKA e PKC - Pereira, Erik Willyame Menezes (2021)
Background: Chronic orofacial pain is a serious public health problem with a prevalence of 7-11% in the population. This disorder has different etiologies and characteristics that make pharmacological treatment difficult. Natural products have been shown to be a promising source of treatments for the management of chronic pain, as an example the terpenes. The aim of this study was to evaluate the anti-nociceptive and anti-inflammatory effects of one of these terpenes, d- limonene (LIM - a common monoterpene found in citrus fruits) alone and complexed with hydroxypropyl-β-cyclodextrin (LIM/HPβCD) in preclinical animal models. Methods: Orofacial pain was induced by the administration of hypertonic saline on the corneal surface, the injection of formalin into the temporomandibular joint (TMJ), or chronic constriction injury of the infraorbital nerve (CCI-IoN). The study used male Wistar rats and Swiss mice treated with LIM (50 mg/kg), LIM/HPβCD (50 mg/kg), vehicle (control), gabapentin or morphine, and eyes wiping (induced by hypertonic saline), face rubbing (formalin-induced in TMJ) or mechanical hyperalgesia (provoked by CCI-IoN) were assessed. Additionally, ELISA was used to measure TNF-α, and western blot analysis to assess levels of PKAcα, NFκB, p38MAPK and phosphorylated PKC substrates. Serum levels of aspartate aminotransferase (AST) and alanine transferase (ALT) were also evaluated. Results: LIM and LIM/HPβCD significantly reduced (p<0.001) corneal nociception and formalin- induced TMJ nociception. In addition, both substances attenuated (p<0.001) mechanical hyperalgesia in the CCI-IoN model. The antinociceptive effect induced by LIM and HPβCD/LIM was associated with decreased TNF-α levels, downregulation of the NFκB and p38MAPK signalling pathways and reduced PKC substrate phosphorylation and PKA immunocontent. Moreover, the results demonstrated that complexation with HPβCD was able to decrease the therapeutic dose of LIM. Conclusions: LIM was found to be a promising molecule for the treatment of orofacial pain due to its capacity to modulate some important mediators essential to the establishment of pain, and HPβCD can be a key tool to improve the profile of LIM.